PENGARUH KOMUNIKASI DAN DISIPILIN KERJA TERHADAP KINERJA KARYAWAN PADA PURI SARON HOTEL SEMINYAK BALI: Studi pada Puri Saron Hotel Seminyak Bali - Helena I Gst Ayu Putu Pusparini; Made Yudi Darmita; Evevdido Dos Santos (Journal Research of Management, 2020)
This study aims to determine whether communication and work discipline affect employee performance at Puri Saron Hotel Seminyak Bali in this study using a population sample of 110 respondents, employees of Puri Saron Hotel Seminyak Bali and data collected by researchers as many as 75 questionnaires. This study used the T-test and F test. The results showed that communication (X1) and work discipline (X2) had a positive and significant effect on employee performance (Y) on Puri Saron Hotel Seminyak Bali can be seen from the regression coefficient Y = 3.462 + 0.201X1 + 0.621X1 conclusions obtained by communication (X1) have a positive and significant effect on employee performance (Y) on Puri Saron Hotel Seminyak Bali which is shown by the regression coefficient b1X1 which is positive at 0.201 with the value of tcount = 2.231 with sing value. t = 0.023. Work Discipline (X2) has a positive and significant effect on employee performance (Y) in Puri Saron Hotel Seminyak Bali which is shown by the coefficient b2X2 which is positive at 0.621, with a value of t = 6,034 with a sing value. T = 0,000. The independent variable that influences employee performance can be seen in the standardized Coefficients Beta value is the communication variable (X1) that is equal to 0.503 while the work discipline (X2) is 0.683. The magnitude of the influence of communication and work discipline on employee performance at Puri Saron Hotel Seminyak Bali.Keywords: communication, work discipline, and employee performance.